A trend analysis of abstracts published in the Journal of Community Psychology over the years 2003-2007. - Ismail, Tasneem (My University, 2010)
The aim of this study was to investigate several trends within the Journal of Community Psychology over the last five years (January 2003 – December 2007). These trends were organised into four areas: trends in type of publication, methodological trends, topic trends, as well as South African trends. The study utilised both qualitative and quantitative components to ascertain these trends, and can therefore be termed a mixed-method approach. The qualitative component of the study involved the use of a self-created coding system which combined predefined conceptual and theoretical constructs derived from community psychology literature as well as themes emerging from the data set. 242 article abstracts were coded and analysed to ascertain the trends in relation to the aforementioned four focus areas. Following this, the quantitative component of the study involved the analysis of the emergent trends using conceptual content analysis which involved the attainment of frequencies per trend. Additional exploratory Chi-Squared analyses were also utilised to ascertain if any significant relationships existed between the emergent trends. The results yielded indicate that the dominant publication type within the Journal of Community Psychology over this period was empirical articles; the predominant method utilised was positivist/quantitative; the main topic focused on was „mental health and mental illness‟; and the representation of South African authors and studies was minimal (<2%). By analysing these trends, a more comprehensive understanding of contemporary community psychology knowledge production has been provided which has allowed for the field to be critically interrogated. Further to this, the study provides an overview of the current developments in community psychology scholarship more generally, as well as the ways in which South African scholarship is represented within this international publication.